2012
DOI: 10.1088/1367-2630/14/2/023022
|View full text |Cite
|
Sign up to set email alerts
|

Phase coexistence of clusters and islands: europium on graphene

Abstract: The adsorption and equilibrium surface phases of europium (Eu) on graphene on Ir(111) are investigated in the temperature range from 35 to 400 K and for coverages ranging from a small fraction of a saturated monolayer to the second layer by scanning tunnelling microscopy. Using density functional theory including 4f-shell Coulomb interactions and modelling of electronic interactions, excellent agreement with the experimental results for the equilibrium adsorbate phase, adsorbate diffusion and work function is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 50 publications
7
64
0
Order By: Relevance
“…Most of the metal adatoms favor the H-site, while Pb, Cu, Au adatoms prefer the T-site and Cr, Pd, Pt, and Ag adatoms take the B-site. The adsorption energies (E a ) and diffusion barrier (ΔE) for various metal adatom adsorbed on graphene obtained from DFT calculations of Liu et al are shown in Figure 8a,b, respectively, in comparison with other works [29,31,38,40,45,[48][49][50][51]55]. The metals in the horizontal axis are arranged in the order of group I-IV metals, 3d-transition metals, group 10 transition metals, noble metals, as well as rare earth metals.…”
Section: Energeitcs Of Metals On Graphenementioning
confidence: 79%
See 2 more Smart Citations
“…Most of the metal adatoms favor the H-site, while Pb, Cu, Au adatoms prefer the T-site and Cr, Pd, Pt, and Ag adatoms take the B-site. The adsorption energies (E a ) and diffusion barrier (ΔE) for various metal adatom adsorbed on graphene obtained from DFT calculations of Liu et al are shown in Figure 8a,b, respectively, in comparison with other works [29,31,38,40,45,[48][49][50][51]55]. The metals in the horizontal axis are arranged in the order of group I-IV metals, 3d-transition metals, group 10 transition metals, noble metals, as well as rare earth metals.…”
Section: Energeitcs Of Metals On Graphenementioning
confidence: 79%
“…Recently, Ir, Pt, W, Re, Co, Eu, Au, AuIr, and FeIr nanoislands have been grown on the graphene moiré structure on Ir(111) substrate as shown by Michely et al [16,[27][28][29][79][80][81]. Noble metal clusters on graphene prepared by chemical methods have also been shown to enhance the electrocatalytic activity [65][66][67][68][69][70].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only for higher temperatures, dimers form by lateral attachment of adatoms diffusing toward each other from far distances. This is indicative of a repulsion between the atoms that can only be overcome for T > 50 K. This repulsion is very likely electrostatic, since rare-earth atoms, similar to alkali atoms [24,31], are expected to transfer electrons to graphene [25,31,32], resulting in positively charged adatoms.…”
Section: A Statistical Analysismentioning
confidence: 99%
“…We simplify the potential landscape induced by the moiré by attributing a global minimum in the atop stacking area and the same height to hollow and bridge stacked regions. The repulsion is described by a screened Coulomb potential [34,35] since a pure Coulomb potential turns out to be too long-ranged, and dipolar interactions are too weak at the relevant distances, as estimated from dipole moments calculated for rare-earth atoms [31,32] and alkali metals [31,34] on freestanding graphene. The screening effect is due to the redistribution of the electrons in graphene around the charged adatoms, yielding a lower effective charge for the repulsion and a faster decay.…”
Section: B B B B a A A A A A A A A A A A A A A A A A A A A A A A A A mentioning
confidence: 99%